Importance of tenure and governance for multifunctional landscapes - Meinzen-Dick, Ruth S.; Zhang, Wei (International Food Policy Research Institute, 2025)
Agricultural production occurs within landscapes that combine crop fields along with other types of land uses such as animal grazing areas, forests, agroforestry areas, wetlands, and water bodies, each influencing and being influenced by the others (Altieri et al., 2018). While these are often considered separately, there are complex flows of resources—including nutrients, water, energy, and labor—among these different components. What is done on one area will affect others. For example, use of pesticides to increase production of certain crops can kill pollinators that are needed for other crops, or pollute waters that affect fish downstream. Positive externalities are also possible: afforestation can reduce soil erosion and affect the timing and volumes of water flows.